Forest landscape restoration in Ethiopia: Progress and challenges - Kassa, H.; Abiyu, A.; Hagazi, N.; Mokria, M.; Kassawmar, T.; Gitz, V. (Frontiers Media, 2022)
The government of Ethiopia has made an ambitious plan of building a carbon-neutral and middle-income economy by 2030. In 2016, the country pledged to restore 15 million hectares of degraded landscapes as part of the African Forest Landscape Restoration Initiative (AFR 100). A total of three major forest landscape restoration (FLR) initiatives have been used to achieve this target: participatory forest management (PFM) to engage communities in sustainably managing natural forests; area enclosures/exclosures (AEs) to socially fence hillsides and degraded communal lands and allow these areas regain their productive potential; and sustainable land management program and the Green Legacy Initiative (SLM-GLI) that aim at conserving soil and water resources and planting seedlings to increase forest cover. After describing these FLR initiatives, this study evaluated their impacts on land use land cover change over time and assessed them against the six FLR principles by selecting nationally relevant criteria under each principle. The results showed that the FLR initiatives were rated rather low in terms of focusing on and managing landscapes for multiple benefits, in participation and benefits of stakeholders, in ownership and use rights, in employing approaches tailored to the local context, and in managing adaptively for long-term resilience. Concerning impacts, varying trends were observed for different areas, time periods, and restoration types. Recognizing and mitigating the limitations of these initiatives together with addressing site-specific drivers will improve the conservation and livelihood outcomes of FLR initiatives in Ethiopia. It is hoped that the findings of the study will inform FLR practitioners in other countries on the practical use of FLR principles in assessing the impacts of FLR initiatives.